Immunotherapeutic implications of negative regulation by protein tyrosine phosphatases in T cells: the emerging cases of PTP1B and TCPTP - Perez-Quintero, Luis Alberto; Abidin, Belma Melda; Tremblay, Michel L. (Frontiers in Medicine, 2024)
In the context of inflammation, T cell activation occurs by the concerted signals of the T cell receptor (TCR), co-stimulatory receptors ligation, and a pro-inflammatory cytokine microenvironment. Fine-tuning these signals is crucial to maintain T cell homeostasis and prevent self-reactivity while offering protection against infectious diseases and cancer. Recent developments in the understanding of the complex crosstalk between the molecular events controlling T cell activation and the balancing regulatory cues offer novel approaches for the development of T cell-based immunotherapies.Among the complex regulatory processes, the balance between protein tyrosine kinases (PTK) and the protein tyrosine phosphatases (PTPs) controls the transcriptional and metabolic programs that determine T cell function, fate decision, and activation. In those, PTPs are de facto regulators of signalling in T cells acting for the most part as negative regulators of the canonical TCR pathway, costimulatory molecules such as CD28, and cytokine signalling. In this review, we examine the function of two close PTP homologs, PTP1B (PTPN1) and T-cell PTP (TCPTP; PTPN2), which have been recently identified as promising candidates for novel T-cell immunotherapeutic approaches. Herein, we focus on recent studies that examine the known contributions of these PTPs to T-cell development, homeostasis, and T-cell-mediated immunity. Additionally, we describe the signaling networks that underscored the ability of TCPTP and PTP1B, either individually and notably in combination, to attenuate TCR and JAK/STAT signals affecting T cell responses. Thus, we anticipate that uncovering the role of these two PTPs in T-cell biology may lead to new treatment strategies in the field of cancer immunotherapy.This review concludes by exploring the impacts and risks that pharmacological inhibition of these PTP enzymes offers as a therapeutic approach in T-cell-based immunotherapies.